Synthesis of arylbenziodoxoles using pseudocyclic benziodoxole triflate and arenes; Arkivoc; Vol. 2020, Part (iv) : Special Issue 'Hypervalent Iodine Chemistry, part 1' - Yoshimura A. Akira; Larson M. Scott; Frahm G. B. Gunnar; Huss Ch. D. Christopher; Rohde G. T. Gregory; Nemykin V. N. Victor; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Saito A. Akio; Zhdankin V. V. Viktor Vladimirovich (2020, 2020)
Title screen